A novel maternally inherited 8q24.3 and a rare paternally inherited 14q23.3 CNVs in a family with neurodevelopmental disorders. (10th April 2015) - Hu, Jie; Sathanoori, Malini; Kochmar, Sally; Azage, Meron; Mann, Susan; Madan‐Khetarpal, Suneeta; Goldstein, Amy; Surti, Urvashi
<x xml:space="preserve">Abstract</x> A 7‐year‐old female with developmental delay (DD), autism spectrum disorder (ASD), intellectual disability (ID), attention deficit hyperactivity disorder (ADHD), and seizures was referred to our laboratory for oligomicroarray analysis. The analysis revealed a 540 kb microdeletion in the chromosome 8q24.3 region (143, 610, 058–144, 150, 241) encompassing multiple genes. Two siblings of the proband were also analyzed. The proband's older sister with DD, seizures, and ASD has a 438 kb intragenic microdeletion of the GPHN gene in the chromosome 14q23.3 region (67, 105, 512–67, 543, 291) containing multiple exons, while the proband's older brother with DD, ASD, ID, and ADHD has both the 8q24.3 and the 14q23.3 deletions. All three siblings have a normal karyotype at the 650 G‐band level of resolution. Parental FISH analysis indicates that the mother is a carrier for the 8q24.3 deletion and the father is a carrier for the 14q23.3 deletion. The 8q24.3 deletion seen in our patients has not been reported in the literature, while the small deletions of the 14q23.3 region involving multiple exons of the GPHN gene have been reported in a handful of patients in a recent study. The size of the 8q24.3 deletion and its genomic content, as well as the maternal family history, strongly suggest the association between the deletion and the neurodevelopmental disorders. Our study also provides more evidence in support of the association between GPHN deletion and neurodevelopmental disorders. © 2015 Wiley Periodicals, Inc.